Fit By Founding, Fit By Adaptation: Reconciling Conflicting Organization Theories With Logical Formalization - Péli, Gábor (Academy of Management Review, 2009)
Organizational populations can alter via the individual adaptation of incumbent organizations or via new entrants that match actual conditions. The Red Queen and inertia theories of organizational ecology represent these two forms of population adjustment. However, some of their conclusions contradict each other in their present state. I reconcile their arguments by refining the concepts of environmental change and adaptation. The main points are captured by logical formalization that derives the modified, noncontradicting conclusions as theorems.